The Italian ICD-11 field trial: clinical utility of diagnostic guidelines for schizophrenia and related disorders - Luciano, Mario (Int J Ment Health Syst, 2020)
BACKGROUND: The 11th revision of the International Classification of Diseases and Related Disorders (ICD-11) has been released. In order to test the clinical consistency and the clinical utility of the proposed guidelines the World Health Organization (WHO) has carried out the Ecological Implementation Field Studies in various countries. In this paper the results of the Italian field trials on the clinical utility of the ICD-11 diagnostic guideline concerning schizophrenia and related disorders will be presented. METHODS: In Italy, field trials have been carried out at the Department of Psychiatry of the University of Campania “L. Vanvitelli”. All patients showing any psychotic symptom and referring to the outpatient and inpatient units have been recruited. Patients were interviewed by two clinicians with whom they had not had any prior clinical contact. At the end of each interview, clinicians were asked to complete 12 questions about the clinical utility of the diagnostic guidelines as applied to each patient. RESULTS: Fourteen clinicians and 100 patients have been involved. The ICD-11 clinical guidelines were perceived as easy to use, with an adequate goodness of fit, clear and understandable and with an adequate level of details and specificity to describe the essential features of the diagnoses. Clinicians rated very positively their usefulness in describing the threshold between patient’s disorder and normality. Despite still very positive, the guidelines have been perceived as less useful to select a treatment, to assess patients’ prognosis and to communicate with other mental health professionals. CONCLUSIONS: The 11th revision of the chapter on Mental, Behavioural and Neurodevelopmental Disorders has made substantive changes to the conceptualization of mental disorders which could have impacted on their reliability and clinical utility. Results of the Italian field studies, in line with those reported by the international sample, highlight that ICD-11 has been rated as highly clinically useful by participating clinician, more than the ICD-10. This could be considered a good reason to be optimistic about the implementation of the ICD-11 among global clinicians. Trial registration The study has been approved by the Ethical Review Board of the University of Campania “L. Vanvitelli” (N. 416, 2016)